Effect of eicosapentaenoic acid on bovine cumulus–oocyte complex in vitro - Nikoloff, Noelia (2017)
The aim of the present study was to investigate the effects of eicosapentaenoic acid (EPA) supplementation during in vitro maturation (IVM) of bovine oocytes. The concentrations tested in all experiments were 1 nM, 1 μM, and 1 mM EPA. The effect of EPA was evaluated on cumulus‐oocyte complexes (COC) by oocyte maturation (cumulus expansion area and oocyte nuclear maturation), genotoxicity [single cell gel electrophoresis (SCGE)], and cytotoxicity (apoptosis, viability, and MTT assays) end points. The maturation parameters were affected by exposure of COC to different EPA concentrations in the IVM medium. Cumulus expansion area increased in the presence of 1 nM EPA (P < 0.05) whereas addition of 1 nM EPA (P < 0.05) decreased cumulus expansion after 24 h of IVM. Moreover, the maturation rate significantly decreased when 1 mM of EPA was assayed (P < 0.001). EPA at 1 nM induced genotoxic and cytotoxic effects on bovine cumulus cells (CC) and primary DNA lesions (P < 0.001). A significant increase in the frequency of apoptotic (P < 0.01) and necrotic (P < 0.001) cells was observed after 24 h of treatment with 1 nM, 1 μM, and 1 mM EPA. Mitochondrial activity was altered with 1 mM EPA (P < 0.001). We inferred that optimal oocyte quality was partially dependent on the presence of adequate EPA concentrations; EPA could be beneficial to improve oocyte quality in the maturation process, because low concentration tested (1 nM EPA) improved cumulus expansion.